Discrete duality finite volume scheme for solving Heston model - Handlovičová, Angela (Proceedings of the Conference Algoritmy, 2016)
New numerical scheme for tensor diffusion equation based on discrete duality finite volume (DDFV) method is derived.  Tensor diffusion equation represents an important model in many fields of science. We focused our attention to the problem which arises in financial mathematics and is known as 2D Heston model see [5]. Existence and uniqueness of numerical solution is derived and numerical experiment using proposed  scheme are included.